2011
DOI: 10.1177/0956797611398495
|View full text |Cite
|
Sign up to set email alerts
|

Third Parties, Violence, and Conflict Resolution

Abstract: Although researchers know much about the causes of aggression, they know surprisingly little about how aggression leads to violence or how violence is controlled. To explore the microregulation of violence, we conducted a systematic behavioral analysis of footage from closed-circuit television surveillance of public spaces. Using 42 incidents involving 312 people, we compared aggressive incidents that ended in violence with those that did not. Behaviors of antagonists and third parties were coded as either esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 26 publications
6
82
1
Order By: Relevance
“…Furthermore, our findings showed that for a given pair of individuals, the likelihood of consolation increased with the number of other individuals present. This contradicts the hypothesized bystander effect and confirms recent evidence that violence may diminish the bystander effect [42] or even reverse it [4]. Unlike prior findings on consolation in bonobos [12], our findings demonstrate that the physical distance between two individuals does not affect the probability of consolation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, our findings showed that for a given pair of individuals, the likelihood of consolation increased with the number of other individuals present. This contradicts the hypothesized bystander effect and confirms recent evidence that violence may diminish the bystander effect [42] or even reverse it [4]. Unlike prior findings on consolation in bonobos [12], our findings demonstrate that the physical distance between two individuals does not affect the probability of consolation.…”
Section: Discussionsupporting
confidence: 60%
“…Specifically, we analyzed the immediate aftermath of nonfatal robberies to look for adult human consolation. Surveillance camera footage offers a unique and ethically sound way of studying adult behavior in high-danger contexts [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Note that we obtained descriptions of aggressive acts and ratings of intoxication for each person involved in incidents of aggression. This yielded considerably more detail about the aggressive incidents than was available in previous research on barroom aggression (Graham, et al, 1980; 2000; Homel, et al, 2004; Homel and Clark, 1994; Levine, et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Research demonstrates that third parties frequently enter interpersonal conflicts and often affect the outcomes (e.g., Cooney, 1998; Graham and Wells, 2003; Levine, Taylor, and Best, 2011; Wells and Graham, 1999; Planty, 2002). Third parties can act as agents of social control who mediate the conflict or they can make conflicts worse by either encouraging the main participants to be aggressive or by entering the fray themselves (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation